Effectiveness of a Values Clarification Program on Ethical Reasoning and Identity Stability - Lee, Angel; Yildiz, Emre; Chaudhary, Aman Ullah (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to evaluate the effectiveness of a structured values clarification program on enhancing ethical reasoning and identity stability among young adults.Methods and Materials: A randomized controlled trial was conducted with 30 participants from Turkey, randomly assigned to either an experimental group (n = 15) or a control group (n = 15). The experimental group participated in a six-session, 90-minute values clarification program, while the control group received no intervention. Ethical reasoning was measured using the Defining Issues Test, Second Edition (DIT-2), and identity stability was assessed with the Ego Identity Process Questionnaire (EIPQ). Assessments were conducted at three time points: pretest, posttest, and five-month follow-up. Data were analyzed using repeated measures analysis of variance (ANOVA) and Bonferroni post-hoc tests with SPSS version 27.Findings: Results showed significant improvements in both ethical reasoning and identity stability in the experimental group compared to the control group. Ethical reasoning scores increased from a mean of 28.47 (SD = 4.36) at pretest to 35.63 (SD = 5.02) at posttest, and remained high at follow-up (M = 34.51, SD = 5.11). Identity stability scores in the experimental group rose from 91.27 (SD = 7.54) at pretest to 105.46 (SD = 6.72) at posttest, with a follow-up mean of 103.88 (SD = 7.13). ANOVA results indicated significant time × group interaction effects for ethical reasoning (F(2, 54) = 22.15, p = .001, η² = .49) and identity stability (F(2, 54) = 23.55, p = .001, η² = .52). Bonferroni tests confirmed that these improvements were statistically significant and sustained over time.Conclusion: The findings suggest that the values clarification program is an effective intervention for promoting ethical reasoning and strengthening identity stability, with lasting effects observable at a five-month follow-up.